The Patristic Text in the Confessional Age (16th-17th centuries) : Erudition, Theology, Censorship - Quantin, Jean-Louis (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This volume follows the paradoxical trajectory of patristic studies in early modern Europe, from their full confessionalization in the mid-16th century to the emergence of 'fringe patristics' within minority groups in the early 18th century. The appeal to the Fathers, which was meant to buttress established orthodoxies, powerfully contributed to their dissolution in the internal strifes of 17th-century churches, especially on grace and predestination. An ample English introduction, with very rich notes, surveys the flourishing field of patristic reception and advocates for a historical, rather than theological or literary, approach.